Current law year book, 1985 : being a comprehensive statement of the law of 1985 - Allsop, Peter (London : Sweet & Maxwell, 1986)
This volume is the Current law yearbook for 1985. It covers the law from January 1 to December 31 of the year.
rpm 25/01/2019
Ref
Keywords: Law; Law reports, digests, etc; Droit; Great Britain